2021
DOI: 10.1001/jamaoncol.2021.2224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carboplatin and Isotretinoin in Children With High-risk Medulloblastoma

Abstract: IMPORTANCE Brain tumors are the leading cause of disease-related death in children. Medulloblastoma is the most common malignant embryonal brain tumor, and strategies to increase survival are needed.OBJECTIVE To evaluate therapy intensification with carboplatin as a radiosensitizer and isotretinoin as a proapoptotic agent in children with high-risk medulloblastoma in a randomized clinical trial and, with a correlative biology study, facilitate planned subgroup analysis according to World Health Organization co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 30 publications
2
88
1
Order By: Relevance
“…Being a constant work in progress, new disease subgroups and risks groups have been implemented in the analysis of ongoing clinical trials concerning therapy reduction in low-risk and treatment intensification in high-risk patients. Concerning the latter, a prospective randomized trial for high-risk patients from the Children’s Oncology Group involving concomitant Carboplatin during radiotherapy showed a survival benefit in the Carboplatin arm in group 3 patients only [ 86 ].…”
Section: Results Of Clinical Trialsmentioning
confidence: 99%
“…Being a constant work in progress, new disease subgroups and risks groups have been implemented in the analysis of ongoing clinical trials concerning therapy reduction in low-risk and treatment intensification in high-risk patients. Concerning the latter, a prospective randomized trial for high-risk patients from the Children’s Oncology Group involving concomitant Carboplatin during radiotherapy showed a survival benefit in the Carboplatin arm in group 3 patients only [ 86 ].…”
Section: Results Of Clinical Trialsmentioning
confidence: 99%
“…Haematological toxicity was dose-limiting while ototoxicity was acceptable. This regimen resulted in a favourable 5-year PFS rate of 71% and was the basis for the later randomised phase III Children’s Oncology Group ACNS-0332 study [ 70 ]. Recently, this study has demonstrated an improvement of EFS by 19% at 5-years for children with high-risk group 3 medulloblastoma receiving concurrent carboplatin during 36 Gy craniospinal irradiation.…”
Section: Aims and Design Of The Trial Stratamentioning
confidence: 99%
“…Indeed, our findings suggest that when correcting for subgroup, comparable outcomes can be achieved, and subgroup-specific strategies can and should be implemented in LMIC settings. Specifically, recent studies from the Children's Oncology Group have suggested that carboplatin radiosensitization significantly improves outcome in metastatic group 3 34 and reductions in radiotherapy to 18 Gy have poor survivals restricted to group 4, 35 suggesting that subgroup-specific therapies should not be restricted to HICs. Although a limitation for many LMIC centers is lack of a constant twinning partner, we would advocate for protocol implementation in LMIC centers to ensure uniform staging, and being cognizant of the risks of delaying therapy, specifically developing protocols unique to the limitations of each center.…”
Section: Discussionmentioning
confidence: 99%